Hubungan Body Image dengan Harga Diri pada Remaja Putri Penggemar Kpop di Komunitas A.R.M.Y Medan - Nini Sri Wahyuni; Anisty Auriella (Mahesa Research Center, 2021)
This study aims to determine the relationship between body image and self esteem in Adolescent of K-pop fans in the A.R.M.Y Medan Community. Researchers used quantitative research methods with respondents being Kpop fan girls who joined the A.R.M.Y Medan Community where the number of young women who were taken as research subjects was 100 people. The measuring instrument in this study used a body image scale of 26 items (reliability: 0.918) and a self-esteem scale of 32 items (reliability: 0.918). Methods of data analysis using product moment correlation with the help of SPSS version 25.0 to determine the form of the relationship and the value of the body image variable in explaining the variable self-esteem. The results of the data analysis indicate that there is a positive relationship between body image and self-esteem where rxy = 0.432 with a significant p = 0.000 <0.05. So that the rhit value> rtab (0.432> 0.194) is obtained so that the proposed hypothesis is accepted. This means that the hypothesis proposed is that there is a positive relationship between Body Image and Self-esteem in Kpop fans in the A.R.M.Y Medan Community. Self-esteem is formed by Body Image by 18.7%. From this contribution percentage, it can be seen that there are still 81.3% influence from other factors of Self-esteem. Based on the results of empirical calculations, it shows that young women in the A.R.M.Y community in Medan have moderate self-esteem and body image.